Synthesis of Indazoloquinones - W. Sucrow; U. Sandmann (CHIMIA)
The indazolone 1 was prepared and served as a starting material for the synthesis of the quinone 6, structurally related to the mitomycin antibiotics, in five steps via compounds 2 to 5.